Understanding Authentic Followership from Empirical Research: A Scoping Review - Triyo Utomo; Seger Handoyo; Fajrianthi (Psychopreneur Journal, 2024)
Authentic followership is a new concept that has developed in recent years. Authentic followership is a form of follower behavior that emphasizes awareness and authentic desired which are manifested in the initiative to be involved in achieving organizational goals through a sense of ownership, openness, non-defensiveness, and interaction with leaders. This paper aims to find out the definitions of authentic followership, the theories used in discussing authentic followership, and the determinants and effects of authentic followership. The method used is a scoping review. The results show similarities and differences in the definitions of authentic followership. Furthermore, most of the reviewed articles use Self-Determination Theory (SDT) in explaining the role of authentic followership in other aspects. The third result of the literature review shows several determinants and effects of authentic followership. There are three identifiable determinants (leadership style, psychological attributes of followers, and psychological attributes of leaders). Meanwhile, the two effects of authentic followership are types of performance and psychological attributes of followers. The results of this review can be used as a basis for other scholars to conduct research on authentic followership.